Scaling Concept Graphs in MathScale Enhances MATH Dataset Accuracy - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 14 peer-reviewed papers addressing the following research question: To what extent does scaling the size of the concept graph in MathScale improve the model's accuracy on the MATH dataset compared to baselines without structured knowledge extraction. 0 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 3.7/10. This report is a machine-gene
Machine-generated literature synthesis.